The effects of TGF-β receptor I inhibitors on myofibroblast differentiation and myotube formation - Wang, Zhihao; Ongkosuwito, Edwin. M.; Von den Hoff, Johannes W.; Wagener, Frank A. D. T. G. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionFibrosis frequently occurs in muscle wounds, ultimately leading to suboptimal function. This study investigates the effects of TGF-βRI inhibitors AZ12799734, Galunisertib, and SM16, on myofibroblast differentiation and myotube formation.MethodsHuman gingival fibroblasts were treated with TGF-β1 (0, 1, 5, and 10 ng/mL) to induce myofibroblasts. Then, fibroblasts were incubated with TGF-βRI inhibitors (0, 1, 5, 10, and 20 µM) together with 10 ng/mL TGF-β1. Myofibroblast marker expression was assessed using RT-PCR (day 3), while myofibroblast differentiation was analyzed by immunofluorescence staining for α-SMA (day 6). C2C12 myoblasts were also cultured with TGF-βRI inhibitors, and gene expression (day 3) and myotube formation (day 6) were analyzed.ResultsTGF-β1 (10 ng/mL) increased the proportion of myofibroblasts from 9.3% ± 3.5% to 38.1% ± 4.4%, which was reduced by all TGF-βRI inhibitors even at 1 µM [for example, Galunisertib 23.5% ± 2.1% (p < 0.05)]. All inhibitors reduced ACTA2 and COL1A1 gene expression, while only AZ12799734 and SM16 inhibited Ki-67 expression. In C2C12 cultures, AZ12799734 and SM16 reduced the fusion index, whereas Galunisertib did not. Moreover, only Galunisertib increased myotube size from 0.09 ± 0.01 to 0.13 ± 0.01 mm2/nucleus (p < 0.05). Galunisertib inhibited MyoD gene expression (at 20 µM), but not MyoG nor MyHC.DiscussionGalunisertib may have potential for improving muscle wound healing following injury.